2017
DOI: 10.1016/j.fgb.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biotic and abiotic factors on the expression of fungal effector-encoding genes in axenic growth conditions

Abstract: a b s t r a c tIn phytopathogenic fungi, the expression of hundreds of small secreted protein (SSP)-encoding genes is induced upon primary infection of plants while no or a low level of expression is observed during vegetative growth. In some species such as Leptosphaeria maculans, this coordinated in-planta upregulation of SSP-encoding genes expression relies on an epigenetic control but the signals triggering gene expression in-planta are unknown. In the present study, biotic and abiotic factors that may rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Fungal genes that are induced during infection are transcriptionally regulated presumably in response to a combination of nutrition conditions, plant‐derived inducing compounds, or infection‐related fungal development (Basse et al., 2000; Meyer et al., 2017; Van den Ackerveken et al., 1994; van der Does et al., 2008). Earlier studies by Sweigard et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal genes that are induced during infection are transcriptionally regulated presumably in response to a combination of nutrition conditions, plant‐derived inducing compounds, or infection‐related fungal development (Basse et al., 2000; Meyer et al., 2017; Van den Ackerveken et al., 1994; van der Does et al., 2008). Earlier studies by Sweigard et al.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal genes that are induced during infection are transcriptionally regulated presumably in response to a combination of nutrition conditions, plant-derived inducing compounds, or infection-related fungal development (Basse et al, 2000;Meyer et al, 2017;Van den Ackerveken et al, 1994;van der Does et al, 2008). Earlier studies by Sweigard et al (1995) showed that PWL2 transcripts were not detectable when M. oryzae was grown in complete, minimal, or nitrogendepleted medium, thus excluding these nutrition conditions as a cue to induce PWL2 expression.…”
Section: Pwl2 Expression Is Activated By An Unknown Signal In Livinmentioning
confidence: 99%
“…It is suspected that SSPs may play a role in the host adaptation of fungi but this aspect remains unclear [114]. However, their importance in the successful interaction with the host has been reported for various fungal symbionts and pathogens [114][115][116][117]. The presence of large variations in the gene number of SSPs within phytopathogenic fungi suggested that the molecular function of SSPs could be linked to the different infection strategies developed by such microorganisms [114].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of large variations in the gene number of SSPs within phytopathogenic fungi suggested that the molecular function of SSPs could be linked to the different infection strategies developed by such microorganisms [114]. In Leptosphaeria maculans, the expression of SSPs is regulated during plant infection and is also influenced by physical parameters such as the presence of antibiotics from prokaryotes in the rhizosphere [117]. This suggests that fungal SSPs, in addition to their role in plant interaction, may participate in ecological niche colonization by shaping plant-associated microbial interactions [118].…”
Section: Discussionmentioning
confidence: 99%
“…In a natural environment, there is continuous fluctuation of temperature, and moisture as well as high spatial variation in pH but also in multiple other abiotic factors. Such abiotic factors can affect the AM fungal growth as well as the mycorrhizal response (MR) (Wang et al, 1993; Heinemeyer and Fitter, 2004) and have seen to alter the gene expression of fungi (Meyer et al, 2017). (2, 3) Lack of biotic stimuli : the main benefit of TRC is the ability to grow AM fungi under sterile conditions that allows for uncontaminated propagation of the desired species/isolate.…”
Section: Introductionmentioning
confidence: 99%